Takotsubo's Long Shadow - Lenkov, Pam (Ars Medica, 2020)
A takotsubo is a type of trap used to capture octopus. Its relevance to clinical medicine is in the specific syndrome named for it, Takotsubo cardiomyopathy, whereby the (grief-stricken or stressed) heart balloons out and assumes a similar shape to this trap.